Persistent Sterile Peritoneal Inflammation After Catheter Removal for Refractory Bacterial Peritonitis Predicts Full-Blown Encapsulating Peritoneal Sclerosis - Wong, Yuk-Yi (Multimed Inc, 2013)
♦ Background: Encapsulating peritoneal sclerosis (EPS) is the most serious complication of peritoneal dialysis, having high morbidity and mortality. To improve outcomes, early diagnosis is needed to direct treatment during the early inflammatory phase. However, in the early inflammatory phase, clinical features are nonspecific, and no reliable diagnostic criteria have been established. Because bacterial peritonitis and termination of dialysis are two important risk factors triggering the progression of EPS, patients with refractory bacterial peritonitis necessitating dialysis catheter removal are at particularly high risk of developing EPS. Many of these patients might indeed experience non-resolving sterile peritonitis (probably the inflammatory phase of EPS) before progression to full-blown disease (that is, the presence of intestinal obstruction). We undertook a retrospective study to compare, in this particular situation, the clinical characteristics of patients with or without sterile peritoneal inflammation, assessing their clinical outcomes in terms of short-term mortality and the chance of developing full-blown EPS. ♦ Methods: Our retrospective review included 62 patients whose dialysis catheter was removed because of refractory peritonitis between January 2005 and December 2010. ♦ Results: Of the 62 patients identified, 39 (63%) had persistent sterile peritoneal inflammation (“high-risk” group, n = 39), and 23 (37%) had resolution of inflammation without significant intra-abdominal collection after catheter withdrawal (“control” group, n = 23). Compared with the control group, the high-risk group had a significantly longer PD duration (71.6 ± 43.3 months vs 42.3 ± 29.9 months, p = 0.003), a higher dialysate-to-plasma ratio (D/P) of creatinine (0.768 ± 0.141 vs 0.616 ± 0.091, p = 0.004), and a higher computed tomography score for EPS (7.69 ± 2.98 vs 1.00 ± 1.00, p < 0.001). During the 6-month study period, the high-risk group had a higher chance of developing full-blown EPS (31% vs 0%, p = 0.002) and a higher 6-month all-cause mortality (36% vs 4.3%, p = 0.004). ♦ Conclusions: Persistent sterile peritoneal inflammation was common after dialysis catheter removal for refractory bacterial peritonitis, and the patients with such inflammation were at high risk of progression to full-blown EPS.